ENTREPRENEURSHIP POLICY IN NIGERIAN UNIVERSITIES AS A DETERMINANT OF ENTREPRENEURIAL INTENTIONS AMONG FRESH GRADUATES - Isah, Emmanuel A.; Orji, Christopher Michael (African Journal of Social and Behavioural Sciences, 2025)
Entrepreneurial intentions refer to an individual’s conscious and deliberate plan to start a new business venture in the future. A complex interplay of psychological, social, and environmental factors shapes these intentions. Entrepreneurial intention is considered the single best predictor of entrepreneurial behavior, as it precedes and motivates the actual act of business creation. The theory of planned behaviour (TPB) remains a dominant framework in explaining entrepreneurial intentions, emphasising the roles of attitude toward entrepreneurship. In the Nigerian context, entrepreneurial intentions among university graduates are supposedly influenced by their exposure to entrepreneurship education. The perceived feasibility and desirability of entrepreneurship were interrogated. A successful enhancement of entrepreneurial intentions is linked to policies that seek to transform Nigerian university entrepreneurial education to new ventures among graduates. How aware are graduates of these policies, and how adequate are they in fostering entrepreneurial intentions? The study used a sample size of 864 respondents, drawn from among university fresh graduates in Nigeria. A structured questionnaire, Entrepreneurship Policy & Entrepreneurial Intention Questionnaire for Fresh Graduates -EPEIQ, was developed by the authors for all participants. The study reveals significant gaps in awareness, delivery, and the practical impact of entrepreneurship policies among fresh graduates from Nigerian universities. While students show moderate recognition of policy intentions and course outcomes, the lack of clarity, communication, and facilitator alignment threatens the effectiveness of these initiatives. It was recommended, among others, that a Campus-Based Policy Awareness Campaign be carried out to sensitize undergraduates on the propriety of entrepreneurship. Universities should host regular seminars, digital outreach, and interactive sessions that demystify entrepreneurship policies and showcase success stories. The lecturers and facilitators need to ensure they understand and can effectively communicate the goals of entrepreneurship education. finally, create dedicated funding pools, incubation centres, and mentorship networks specifically for fresh graduates, with simplified access criteria and ongoing business development support.